1999
DOI: 10.1080/13102818.1999.10819015
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration Possibilities of Bulgarian Bean Cultivars Plovdiv 11M and Dobrudjanski 7

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…McClean et al (55) and Klu (43) regenerated bean plants via direct organogenesis from cotyledonary node tissue and histological studies revealed that buds developed from subepidermal parenchyma cells of the node, confirming the adventitious nature of these structures. Y ancheva et al (82) reported similar results. The process of bean regeneration in their investigation strongly depends on the genotype, type of the explants, type of the cytokinins, duration of the subcultures and inhibition of the phenols secreted during the cultivation into the medium.…”
Section: A) Micropropagation and Morphogenesissupporting
confidence: 82%
“…McClean et al (55) and Klu (43) regenerated bean plants via direct organogenesis from cotyledonary node tissue and histological studies revealed that buds developed from subepidermal parenchyma cells of the node, confirming the adventitious nature of these structures. Y ancheva et al (82) reported similar results. The process of bean regeneration in their investigation strongly depends on the genotype, type of the explants, type of the cytokinins, duration of the subcultures and inhibition of the phenols secreted during the cultivation into the medium.…”
Section: A) Micropropagation and Morphogenesissupporting
confidence: 82%